The Lincoln Memorial - Kenney, Karen Latchana; Hunt, Judith A. 1955- (Edina, Minn. : Magic Wagon, 2011)
Presents information on the history and construction of the Lincoln Memorial and explains what different elements of the memorial signify.
A man in thought -- The sixteenth president -- A president dies -- A plan for a memorial -- The statue -- Building the memorial -- Lincoln's first speech -- Lincoln's second speech -- The memorial's symbols -- "I have a dream" -- Visiting the Lincoln Memorial.
Includes index
6 - 9 years
Keywords: Lincoln, Abraham -- 1809-1865 -- Monuments -- Washington (D.C.); Lincoln Memorial (Washington, D.C.); Lincoln Memorial (Washington, D.C.); Washington (D.C.) -- Buildings, structures, etc